(untitled) (Società e diritti, 2018)
The socio-educational project "In Prison Against Gender Violence" is located inside the second House of Reclusion in Milano-Bollate and has been activated by some professionals of the work team of the internal SerT in prison. In addition, the Equality Councilor of the Lombardy Region has granted the patronage of the Lombardy Region to the project itself. The project "In Prison Against Gender Violence", which lasted about three months, was formulated because the prison context, which is the place for the treatment of subjects in anticipation of social reintegration, appears to be a place in which possible to undertake an educational path aimed at the prevention of the phenomenon in question. The operators, aware of the need to sensitize prisoners and detainees on the aforementioned issues, have decided to implement a socio-educational project with the intention of investing resources on prevention and information related to the phenomenon. L’obiettivo del progetto “In Carcere Contro la Violenza di Genere” appare quindi quello di lavorare, con i partecipanti allo stesso, sull’elevazione della percezione del fenomeno della violenza contro le donne, attraverso l’incontro tra i detenuti selezionati e alcuni esperti del tema in oggetto. The objective of the project "In Prison Against Gender Violence" appears therefore to work, with the participants in the same, on the elevation of the perception of the phenomenon of violence against women, through the meeting between the selected prisoners and some experts of the subject in question. Key words: violence, gender difference, prison